Pembentukan Portofolio Optimal Saham berdasarkan Model Markowitz dan Model Indeks Tunggal pada Perusahaan IDX BUMN20 Tahun 2017-2021 - Edi Wijayanto; Moh Iqbal Hidayatullah; Prihatiningsih Prihatiningsih (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2023)
This study aims to analyze the formation of the optimal stock portfolio based on the Markowitz model and the Single Index model in the IDX BUMN20 company in 2017- 2021. The type of research used is applied quantitative descriptive. The secondary data used are the monthly closing price of shares and the monthly JCI as well as the interest rate of Bank Indonesia. The sample in this study were 15 companies. The model used is the Markowitz model and the Single Index model. The results of the analysis show that 1. There are 11 stocks that are included in the optimal portfolio candidates, namely ANTM, BBTN, BBNI, BBRI, BMRI, JSMR, PGAS, PTBA, SMGR, TINS, and TLKM 2. The formation of the optimal portfolio of the Markowitz model consists of eight issuers with the proportions are BMRI 20%, TLKM 20%, BBRI 18%, PTBA 15%, ANTM 11%, JSMR 9%, SMGR 4% and BBTN 3% by providing a portfolio risk level of 0.0002 or 0.02% and the expected return on the portfolio is 0.0050 or 0.5%. 3. The formation of the optimal portfolio of the Single Index model consists of three issuers with the proportions of BBRI at 48%, ANTM at 45%, TINS 7%.